Porous resin for solid phase synthesis and method for producing same
Patent Information
- Application Number
- JP2023514051
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-11-26
- Filing Date
- 2021-02-24
- Publication Date
- 2025-03-05
- Estimated Expiration
- 2041-02-24
Smart Images

Figure 0007640680000012 
Figure 0007640680000013 
Figure 0007640680000014
Abstract
Description
[Technical field]
[0001] The present invention relates to a porous resin and a method for producing the same, the carrier being used in solid-phase synthesis of oligonucleotides, and belonging to the field of producing functional polymer materials. [Background technology]
[0002] In the past few decades, artificially synthesized oligonucleotides have been widely applied in targeted gene therapy. Oligonucleotides are a general term for short-chain nucleotides with about 20 bases, including deoxyribonucleic acid (DNA) and ribonucleic acid (RNA). At present, oligonucleotides are generally synthesized by chemical methods, and the most common method is the solid-phase phosphoramidite triester method. The specific method is to fill a solid-phase synthesis support into a reaction column, and then rapidly flow a solution containing dissolved reactants through the reaction column at a certain pressure to carry out the reaction. In order to improve the reaction efficiency and reduce the generation of impurities, it is necessary to rapidly diffuse the reactants in the solution into the solid-phase synthesis support to react with the active sites, and to rapidly diffuse the reaction products into the solution and remove them. For this reason, the solid-phase synthesis support is required to meet the following requirements: 1. The support must contain a single active site (or reactive group) to which the nucleic acid molecule chain can be linked and which can be decomposed after synthesis is completed. 2. The support must maintain physical and chemical stability during synthesis. 3. The carrier should have a pore size large enough and an ideal pore size distribution to facilitate rapid and unhindered contact between the growing nucleic acid molecule chain and the reagent. 4. The active sites should be uniformly distributed on the carrier to reduce mutual interference between the nucleic acid molecule chains. 5. The phosphoramidite monomers used in oligonucleotide synthesis are sensitive to moisture, and the presence of moisture reduces the reaction efficiency, so the carrier backbone should exhibit a certain degree of hydrophobicity. 6. The carrier has a similar degree of swelling in different solvents, which reduces the dead volume caused by the difference in swelling of synthesis or washing process in different solvents, and is favorable for uniform diffusion of reaction reagents and rapid washing removal of reaction products.
[0003] In the early development of oligonucleotide solid-phase synthesis technology, the commonly used solid-phase synthesis supports are inorganic particles such as pore-controllable glass microspheres (CPG) and modified silica gel, but their shortcomings are obvious, namely, the degree of substitution (loading) is low (generally less than 100 μmmol / g), which limits the production volume of a single batch of oligonucleotides, the utilization rate of equipment is low, and the production cost is high. In order to increase the degree of substitution of the support, Nitto Denko and Ionis jointly applied for the invention patent WO2006029023, which uses styrene, p-acetoxystyrene, and divinylbenzene as polymerization monomers, and uses isooctane and 2-ethylhexanol as pore-forming agents to prepare an organic polymer, which is used as an oligonucleotide solid-phase synthesis support. The degree of substitution of this carrier can reach 100-350 μmmol / g, but its disadvantage is that the reaction efficiency is low when linking a linker in an onium salt condensation system due to the strong non-polarity of the carrier, and the volume of the resin changes significantly when toluene and acetonitrile are used in the synthesis or washing process due to the strong non-polarity, resulting in a large dead volume in the reactor. Later, Nitto Denko Co., Ltd. used styrene, p-acetoxystyrene, divinylbenzene, and (meth)acrylamide derivatives as polymerization monomers in US Patent US8592542. In US Patent US8653152, styrene, p-acetoxystyrene, divinylbenzene, and (meth)acrylonitrile were used as polymerization monomers. By adding a polar monomer during polymerization, an oligonucleotide solid-phase synthesis carrier with a higher degree of substitution (500 μmmol / g or more) was produced. In addition, the addition of a polar monomer is advantageous for adjusting the swelling fluctuation of the carrier in different solvents (toluene, acetonitrile). However, (meth)acrylamide monomers and (meth)acrylonitrile are hydrophilic, so when they are washed with anhydrous solvents (anhydrous acetonitrile), it is difficult to remove the water added in the oxidation step, which affects the efficiency of the synthesis of the next oligonucleotide.In addition, the pore size distribution obtained by forming pores using the solvent method is non-uniform, which leads to poor mass transfer effect and also affects the removal of water and the efficiency of the synthesis of the next oligonucleotide.The Chinese invention patent CN201210562165.9 applied for by Nankai University uses cross-linked polyacrylonitrile or cross-linked polymethacrylonitrile as the basic skeleton of the carrier. The active site is introduced by adding vinyl acetate, acrylic ester or methacrylic ester monomers, and introducing hydroxy or amino through alkaline decomposition or reaction with a compound having two primary amine groups. This patent uses a large amount of polar monomers, which solves the problem of the swelling difference of the resin in different solvents, but the use of a large amount of hydrophilic monomers makes the carrier very hydrophilic, and it becomes even more difficult to remove moisture from the carrier by washing with anhydrous solvent (acetonitrile), which has a huge impact on the synthesis efficiency of the following oligonucleotides.
[0004] In recent years, the research of oligonucleotide drugs has made great progress, so that more and more oligonucleotide drugs have entered the clinical stage.The demand for oligonucleotide synthesis carrier is increasing, and the problems of mass transfer, swelling and polarity that exist in the above-mentioned oligonucleotide carrier make the efficiency of oligonucleotide synthesis low, and the production cost high.Therefore, it is extremely important to develop a porous resin that can synthesize oligonucleotide drugs on a large scale, at low cost and with high efficiency, so as to meet the market demand for oligonucleotide drugs. Summary of the Invention [Problem to be solved by the invention]
[0005] To enable large-scale, low-cost production of oligonucleotides and overcome the shortcomings of conventional supports, such as low mass transfer efficiency, insufficient washing, and large swelling variations in different solvents, the present invention provides a porous resin for solid-phase synthesis and a method for its preparation.
[0006] In order to improve the mass transfer efficiency, the present invention is desirable to realize a suitable pore size and uniform pore size distribution. The present invention uses a high internal phase emulsion as a template to form pores, and compared with conventional pore formation methods such as reverse phase method, phase separation method, and solvent pore formation method, this method can accurately control the pore size and pore size distribution according to the size of the emulsion droplets. The size of the internal phase emulsion droplets can be determined by factors such as the molecular weight, HLB value, and amount of the oil-soluble surfactant. The present invention changes the pore formation method to make the carrier have a suitable pore size and a narrow pore size distribution, which is favorable for the diffusion of reaction reagents in the oligonucleotide synthesis process, improves the reaction efficiency, and reduces the generation of impurities.
[0007] The addition of modified monomers to the polymerization process has the following four effects. First, the polymerization rate of modified monomers is slow, and they cannot undergo homopolymerization, but can only copolymerize with other monomers, which is favorable for the uniform distribution of active sites. Second, by adding a small amount of modified monomers, the swelling property of the resin can be adjusted over a wide range, which can reduce the change in the swelling volume of the support in different solvents and reduce the dead volume inside the reactor in oligonucleotide synthesis. Third, the molecular structure of the modified monomer makes the onium salt-based condensing agent more efficient and ensures the linking efficiency of the linker. Fourth, the modified monomer is more hydrophobic than (meth)acrylamide-based monomers and (meth)acrylonitrile, which can reduce the mass transfer resistance of water in the support, reduce the impact of water on the oligonucleotide synthesis process, and increase the reaction efficiency and yield. [Means for solving the problem]
[0008] The present invention provides a porous resin for solid phase synthesis, the structure of which is represented by the following formula: [ka] (wherein R1=-C or -C-CH2-, R2=-OH, -CH2OH, -NH2, -CH2NH2, -CH2OOC-C6H4-OH, -CH2OOCCH2-C6H4-OH, -(CH2)4OOC-C6H4-OH, -(CH2)4OOCCH2-C6H4-OH, -COONH-C6H4-NH2, -CH2COONH-C6H4-NH2, -COO-C6H4-OH, or -CH2COO-C6H4-OH, and R3=-H, CH3(CH2) n -(n is an integer from 0 to 4), (CH3)2CH(CH2) n -(n is an integer of 0 to 2), (CH3)3C-, or CH3CH2CH(CH3)-, CH3CH2C(CH3)2-, CH3CH2CH2CH(CH3)-, or CH3(CH2) n -O- (n is an integer from 0 to 4).
[0009] In some embodiments, the porous resin for solid phase synthesis is a copolymer having repeating structural units represented by formula (I), formula (II), formula (III), or formula (IV) in its skeleton. [ka] (wherein R4=-C- or -C-CH2-.) [ka] [ka] (wherein R5 is -OH, -CH2OH, -NH2, -CH2NH2, -CH2OOC-C6H4-OH, -CH2OOCCH2-C6H4-OH, -(CH2)4OOC-C6H4-OH, -(CH2)4OOCCH2-C6H4-OH, -COONH-C6H4-NH2, -CH2COONH-C6H4-NH2, -COO-C6H4-OH, or -CH2COO-C6H4-OH.) [ka] (However, R6 is -H, CH3(CH2) n -(n is an integer from 0 to 4), (CH3)2CH(CH2) n -(n is an integer of 0 to 2), (CH3)3C-, CH3CH2CH(CH3)-, CH3CH2C(CH3)2-, CH3CH2CH2CH(CH3)-, or CH3(CH2) n -O- (n is an integer from 0 to 4).
[0010] In some embodiments, the porous resin for solid phase synthesis has a hydroxy or amino content in the range of 100 to 1000 μmmol / g, preferably 400 to 700 μmmol / g.
[0011] In some embodiments, the porous resin for solid phase synthesis has a particle size in the range of 35-200 μm, preferably 50-100 μm.
[0012] In some embodiments, the porous resin for solid phase synthesis has an average pore size of 10 to 200 nm, preferably 40 to 100 nm.
[0013] The present invention also provides The manufacturing process is The present invention discloses a method for producing a porous resin for solid phase synthesis, comprising the steps of: preparing an aqueous phase composed of water, a dispersant, and an inorganic salt; and an oil phase composed of a monovinyl compound, a crosslinking monomer, a functional monomer, a modified monomer, an oil-soluble surfactant, a diluent, and an initiator, the monovinyl compound, the crosslinking monomer, the functional monomer, and the modified monomer being involved in a polymerization reaction and collectively referred to as monomers, and the oil-soluble surfactant and the diluent not being involved in a polymerization reaction and mainly performing a pore-forming function and collectively referred to as pore-forming agents; adding the oil phase to the aqueous phase, stirring and heating to react, and removing the pore-forming agent after the reaction is completed to obtain a porous polymer resin; and further reacting the porous polymer resin to obtain a solid phase synthesis support containing hydroxy or amino as a functional group.
[0014] In some embodiments, the monovinyl compound is an aromatic monovinyl compound, and the aromatic monovinyl compound is styrene and its benzene ring substituted derivatives, alkyl styrenes whose substituents contain 1 to 5 carbon atoms, such as methylstyrene, ethylstyrene, normal propylstyrene, isopropylstyrene, normal butylstyrene, isobutylstyrene, s-butylstyrene, t-butylstyrene, n-pentylstyrene, isopentylstyrene, s-pentylstyrene or t-pentylstyrene; or alkoxy styrenes whose substituents contain 1 to 5 carbon atoms, such as methoxystyrene, ethoxystyrene, propoxystyrene, butoxystyrene or pentyloxystyrene. The preferred monovinyl compound is styrene.
[0015] In some embodiments, the crosslinking monomer is a multifunctional monomer having two or more non-conjugated vinyls, and in the present invention is preferably divinylbenzene, which may be o-divinylbenzene, m-divinylbenzene, p-divinylbenzene, or a mixture of the three.
[0016] In some embodiments, the functional monomer contains both a radically polymerizable double bond and a hydroxy, amino, halogenated group or a group that can be converted to a hydroxy or amino through a reaction. In the oligonucleotide synthesis process, the reactive hydroxy or amino becomes an active site for linking an oligonucleotide, and may be amino, aminoalkyl, hydroxy, hydroxyalkyl, etc. Preferably, it may be primary amino, aminomethyl, hydroxy, methylol, etc. Hydroxystyrene and its derivatives, such as 4-hydroxystyrene, hydroxyalkylstyrene and its derivatives, such as 4-hydroxymethylstyrene; acyloxystyrene and its derivatives, such as 4-acetoxystyrene, benzoyloxystyrene, etc.; aminostyrene and its derivatives, such as 4-aminostyrene, aminoalkylstyrene and its derivatives, such as 4-aminomethylstyrene; haloalkylstyrene monomers, such as 4-(4-bromobutyl)styrene, 4-chloromethylstyrene, etc.; 4-vinylphenyl ester monomers, such as 4-vinyl methylbenzoate, 4-Ethenylbenzeneacetic acid ethyl ester These include, but are not limited to:
[0017] In some embodiments, the functional monomer contains a hydroxyl or amino protecting group, and may be a monomer in which amino or hydroxyl can be formed by directly cleaving the protecting group. For example, acyloxystyrene may be converted to hydroxyl by hydrolysis with an alkali or acid to become an active site for linking an oligonucleotide. There are also monomers that need to be converted to amino or hydroxyl that can function as an active site by a functionalization reaction. For example, haloalkylstyrene may be converted to hydroxyl by hydrolysis or converted to primary amino by Gabriel reaction to become an active site for linking an oligonucleotide. There are also monomers that need to be linked to a linking arm having amino or hydroxyl as an active site. For example, haloalkylstyrene may react with 4-hydroxybenzoic acid or 4-hydroxyphenylacetic acid to generate hydroxyl to become an active site for linking an oligonucleotide. There are also monomers that need to obtain amino or hydroxyl that can become an active site by a combination of the above reactions. For example, in the case of a monomer of a 4-vinylphenyl ester monomer system, it is first hydrolyzed to expose hydroxyl, and then reacted with hydroquinone or p-phenylenediamine to obtain amino or hydroxyl that can become an active site.
[0018] In some embodiments, the modified monomer has both a double bond capable of participating in radical polymerization and two cyanos in the monomer. Such modified monomers cannot homopolymerize, but can only copolymerize with other monomers, including, but not limited to, transbutene dinitrile, 1,4-dicyano-2-butene, etc. In the present invention, preferred is transbutene dinitrile.
[0019] In some embodiments, the initiator is an organic peroxide or azo compound, including, but not limited to, benzoyl peroxide, lauroyl peroxide, t-butylperoxy 2-ethylhexanoate, 2,2'-azobis(2-methylpropionitrile), 2,2'-azobis(2-methylbutyronitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), etc. The amount of initiator used is 0.5-5% of the total weight of the monomers.
[0020] In some embodiments, the oil-soluble surfactant is a surfactant that does not participate in a polymerization reaction and is insoluble or slightly soluble in water, including, but not limited to, one or more combinations of sorbitan trioleate, polyoxyethylene sorbitol beeswax derivatives, sorbitan tristearate, polyoxyethylene sorbitol hexastearate, ethylene glycol fatty acid esters, propylene glycol fatty acid esters, propylene glycol monostearate, sorbitan sesquioleate, polyoxyethylene sorbitol oleate, glyceryl monostearate, hydroxylanolin, sorbitan monooleate, propylene glycol monolaurate, and propylene glycol fatty acid esters. The diluent is an organic solvent that does not participate in the polymerization reaction and is insoluble or slightly soluble in water, including, but not limited to, aromatic hydrocarbons such as benzene, toluene, ethylbenzene, etc.; aliphatic hydrocarbons such as linear, branched or cyclic alkanes having 6 to 12 carbon atoms, such as hexane, heptane, octane, dodecane, isooctane, isododecane, cyclohexane, etc.; halohydrocarbons such as chloroform, chlorobenzene, etc.; esters having 4 or more carbon atoms, such as ethyl acetate, butyl acetate, dibutyl phthalate, etc.; alcohols such as linear, branched or cyclic alkane alcohols having 4 to 12 carbon atoms, such as hexanol, cyclohexanol, octanol, isooctanol, decanol, dodecanol, etc. The oil-soluble surfactants and diluents do not participate in the polymerization reaction and mainly play a pore-forming role, and are collectively referred to as pore-forming agents.
[0021] In some embodiments, the aqueous phase comprises water, a dispersant and an inorganic salt, and the dispersant is a water-soluble polymer, including, but not limited to, one or more of polyvinyl alcohol, hydroxyethyl cellulose, hydroxyethyl methyl cellulose, carboxymethyl cellulose, methyl cellulose, ethyl cellulose, sodium polyacrylate, and polyvinylpyrrolidone. The amount of the dispersant used is 0.1 to 5% of the weight of the aqueous phase. The inorganic salt serves to adjust the density of the aqueous phase while lowering the solubility of each component in the oil phase in the aqueous phase, and disperse the oil droplets more stably in the aqueous phase. The inorganic salt includes, but is not limited to, one or more of sodium chloride, potassium chloride, calcium chloride, sodium sulfate, potassium sulfate, calcium sulfate, and the like. The amount of the inorganic salt used is 20% or less of the amount of the aqueous phase used.
[0022] In some embodiments, the weight ratio of the oil phase to the water phase is set to 1:3 to 1:20 in order to reduce adhesion between resins, increase the conductivity of polymerization heat, improve the utilization rate of the equipment, and increase production efficiency.
[0023] In some embodiments of the invention, each component is present in the following amounts: initially, the monovinyl compound present in the oil phase is 40-95.9% by weight based on the total weight of monomers, the crosslinking monomer present in the oil phase is 2-20% by weight based on the total weight of monomers, the functional monomer present in the oil phase is 2-20% by weight based on the total weight of monomers, the modifying monomer present in the oil phase is 0.1-20% by weight based on the total weight of monomers, the weight of the pore-former present in the oil phase is 15-70% by weight based on the total weight of monomers, the oil-soluble surfactant is 0.1-15% by weight based on the total weight of pore-former, and the diluent is 85-99.9% by weight based on the total weight of pore-former.
[0024] In some more preferred embodiments of the invention, each component is present in the following amounts: initially, the monovinyl compound present in the oil phase is 60-88% by weight based on the total amount of monomers, the crosslinking monomer present in the oil phase is 5-15% by weight based on the total amount of monomers, the functional monomer present in the oil phase is 5-15% by weight based on the total amount of monomers, the modifying monomer present in the oil phase is 2-10% by weight based on the total amount of monomers, and the weight of the pore former present in the oil phase is 25-50% by weight of the total amount of monomers.
[0025] In some embodiments of the present invention, the polymerization temperature is 50 to 90°C, preferably 60 to 85°C.
[0026] In some embodiments of the present invention, the method for preparing a porous resin for solid phase synthesis comprises the steps of: The method includes the steps of: adding a certain amount of purified water to a reactor, adding and dissolving 0.1-5% by weight of a dispersant relative to the weight of the aqueous phase and 20% by weight or less of an inorganic salt relative to the weight of the aqueous phase to obtain an aqueous phase; weighing and uniformly mixing 40-95.9% of a monovinyl compound, 2-20% of a crosslinking monomer, 2-20% of a functional monomer, 0.1-20% of a modified monomer, 15-70% of a pore-forming agent in which 0.1-15% of an oil-soluble surfactant and 85-99.9% of a diluent relative to the weight of the pore-forming agent, and an initiator, so that the weight ratio of the oil phase to the aqueous phase is 1:3 to 1:20, to obtain an oil phase; adding the oil phase to a reactor, stirring, and heating to 50-90°C to react, and after the reaction is completed, removing the pore-forming agent, sieving to collect resin of an appropriate particle size, and vacuum drying to obtain a porous polymer resin. The resin is further reacted to obtain a porous resin having amino or hydroxyl as a functional group.
[0027] In some embodiments of the present invention, the method for preparing a porous resin for solid phase synthesis comprises the steps of: The method includes the steps of: adding a certain amount of purified water to a reactor, adding and dissolving 0.1-5% by weight of a dispersant and 20% by weight or less of an inorganic salt relative to the weight of the aqueous phase to obtain an aqueous phase; weighing and uniformly mixing 60-88% of a monovinyl compound, 5-15% of a crosslinking monomer, 5-15% of a functional monomer, 2-10% of a modified monomer, 25-50% of a pore-forming agent in which 0.1-15% of an oil-soluble surfactant and 85-99.9% of a diluent relative to the weight of the pore-forming agent, and an initiator, so that the weight ratio of the oil phase to the aqueous phase is 1:3 to 1:20, to obtain an oil phase; adding the oil phase to a reactor, stirring, and heating to 60-85°C to react, and after the reaction is completed, removing the pore-forming agent, sieving to collect resin of an appropriate particle size, and vacuum drying to obtain a porous polymer resin. The resin is further reacted to obtain a porous resin having amino or hydroxy functional groups.
[0028] According to the above method, the porous resin for solid phase synthesis of the present invention, i.e., the porous resin containing hydroxy or amino, can be obtained. In the present invention, the content of amino or hydroxy, i.e., the substitution degree, may be obtained by reacting with Fmoc-Leu-OH, removing the Fmoc protecting group, determining the amount of Fmoc removed by colorimetry, and calculating the content of amino or hydroxy in the porous resin.
[0029] In some examples, the specific operation is as follows: 1.0 g of the carrier is accurately weighed and suspended in 7 ml of acetonitrile solution, then 0.5 g of Fmoc-Leu-OH, 0.5 g of HBTU, and 0.5 ml of DIEA are added, and the mixture is reacted at room temperature with stirring for 2 h. After the reaction is completed, the resin is washed successively with acetonitrile (10 ml per use, washed three times) and methanol (10 ml per use, washed three times), and then the resin is baked. 0.1000 g of the resin is accurately weighed and suspended in a 20% piperidine / DMF (v / v) solution, shaken at room temperature for 30 min, filtered, the filtrate is collected, the resin is washed with DMF, and the filtrate is collected. The filtrate is combined, adjusted to a constant volume, diluted by an appropriate factor, and the absorbance at 300 nm is measured. A series of Fmoc-Leu-OH with known concentrations is used to carry out a similar Fmoc removal reaction, and the absorbance is measured to prepare a calibration curve. The amino or hydroxy content in the porous resin is calculated from the calibration curve.
[0030] The degree of substitution of the porous resin is determined by the ratio of the functional monomer to the total amount of monomers, and a series of porous resins with different degrees of substitution can be obtained by adjusting the amount of the functional monomer used. The degree of substitution of the porous resin determines the amount of oligonucleotide synthesis, and if the degree of substitution is too low, the yield of oligonucleotide per rod decreases, and if the degree of substitution is too high, the purity of the oligonucleotide is affected. In the present invention, the range of the degree of substitution of the porous resin is 100 to 1000 μmmol / g, preferably 400 to 700 μmmol / g.
[0031] In the present invention, the particle size of the porous resin is detected by a particle image processing device, that is, the porous resin is uniformly distributed on a slide glass, the carrier particles are magnified by a microscope, the particle images of the porous resin magnified by the microscope are taken by a camera, and the appearance characteristics and particle size of the porous resin are analyzed and calculated by a computer.
[0032] The size of the particle diameter of the porous resin is mainly determined by the type and amount of dispersant in the aqueous phase, the type and amount of pore-forming agent, and the number of revolutions of the stirring in the suspension polymerization process. By adjusting these conditions, the particle diameter of the porous resin can be adjusted. If the particle diameter of the porous resin is too large, on the one hand, the specific surface area of the carrier decreases, the number of active sites per unit area increases, and the purity of the oligonucleotide is adversely affected, and on the other hand, the mass transfer rate in the synthesis process of the oligonucleotide slows down and impurities increase. If the particle diameter of the porous resin is too small, the pressure in the synthesis process is too high, and the cost of the device increases significantly. In the present invention, the particle diameter of the porous resin is in the range of 35 to 200 μm, preferably 50 to 100 μm.
[0033] The average pore size of the porous resin is measured by mercury intrusion porosimetry. That is, 0.1500-0.3000g of sample is accurately weighed and placed in a fully automatic mercury intrusion apparatus AutoPore IV 9500 (Micromeritics Instrument Co.), the contact angle of mercury is set to 130°, the surface tension is set to 485 dyn / cm, and the measurement is performed by mercury intrusion porosimetry under these conditions. The size of the average pore size of the porous resin is mainly determined by the type and amount of pore-forming agent, the amount of crosslinking agent, the reaction temperature and time, etc. The average pore size of the porous resin can be adjusted by adjusting these conditions. If the average pore size of the porous resin is too small, the material transfer becomes difficult and the synthesis efficiency is affected, and if the average pore size of the porous resin is too large, the specific surface area of the porous resin decreases, the active sites per unit area increase, and during the oligonucleotide synthesis process, the increase in nucleosides causes interactions, which affects the purity of the oligonucleotide. In the present invention, the average pore size of the porous resin is 10 to 200 nm, preferably 40 to 100 nm. Effect of the Invention
[0034] Compared with the prior art, the present invention has four main advantages: First, the modified monomer can adjust the polymerization rate, which is favorable for the uniform distribution of active sites; Second, the swelling performance of the resin can be adjusted to reduce the change in swelling volume of the carrier in different solvents; Third, the two cyanos in the structure of the monomer molecule make the onium salt-based condensing agent perform better, and ensure the linking efficiency of the linker; Fourth, compared with the (meth)acrylamide-based monomer used as the "modified monomer" in patent US8592542 and the (meth)acrylonitrile used as the "modified monomer" in patent US8653152, the modified monomer used in the present invention is relatively hydrophobic, and can quickly remove the trace amount of water remaining in the porous resin during the washing process, thereby reducing the impact of water on the oligonucleotide synthesis process and improving the reaction efficiency and yield. In addition, the present invention uses an oil-soluble surfactant to form pores using the water-in-oil emulsion droplets as templates, which allows the size and distribution of pores in the carrier to be precisely controlled, which is favorable for the diffusion of reaction reagents, improves reaction efficiency, and reduces the generation of impurities. [Brief description of the drawings]
[0035] [Figure 1] 1 is a scanning electron microscope image of the carrier in Example 1. [Diagram 2] 1 is a scanning electron microscope image of the carrier in Example 2. [Diagram 3] 1 is a scanning electron microscope image of the carrier in Example 6. [Figure 4] 1 is a scanning electron microscope image of the carrier in Example 9. [Diagram 5] 1 shows the pore size distribution of the support obtained by mercury porosimetry in Example 1. [Figure 6] 4 shows the pore size distribution of the support obtained by mercury porosimetry in Example 2. [Figure 7] 1 shows the pore size distribution of the support obtained by mercury porosimetry in Example 6. [Figure 8] 1 shows the pore size distribution of the support obtained by mercury porosimetry in Example 9. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0036] The technical solutions of the present invention are further illustrated below with reference to specific examples, but the present invention is not limited to these examples. EXAMPLES
[0037] 2L of purified water, 20g of polyvinyl alcohol, and 60g of sodium chloride were added to a 3L reactor equipped with a condenser, a stirrer, and a thermometer, and dissolved to obtain an aqueous phase. 110g of styrene, 10g of divinylbenzene (content 80% by weight), 12g of p-chloromethylstyrene, 8g of transbutenedinitrile, 5g of sorbitan monooleate, 45g of isooctanol, and 2.5g of benzoyl peroxide were weighed and mixed uniformly to obtain an oil phase. The oil phase was added to the reactor, stirred, heated to 80°C, and polymerized for 4 hours. After the reaction was completed, the mixture was washed with hot water, refluxed with ethanol to extract and remove the pore-forming agent, sieved to collect resin with a particle size of 50 to 100 μm, and vacuum dried to obtain a polymeric porous resin with a chlorine content of 550 μmmol / g. 50g of polymeric porous resin and 500ml of N,N-dimethylformamide were put into a 1L reactor equipped with a condenser, a stirrer and a thermometer, and stirred. Then, 30g of phthalimide potassium salt was added, and the temperature was raised to 95°C and reacted for 16 hours. After the reaction was completed, it was cooled to room temperature, and then washed twice with N,N-dimethylformamide, washed with purified water until it became neutral, and then washed three times with absolute ethanol, and the resin was filtered and dried. 200g of absolute ethanol and 50g of hydrazine hydrate were added to the reactor, and the temperature was raised to 75°C and reacted for 16 hours. After the reaction was completed, it was washed three times with a volume ratio of 50:50 ethanol / purified aqueous solution, washed with purified water until it became neutral, then washed three times with absolute ethanol, and the washing liquid was filtered. 200g of absolute ethanol and 50g of concentrated hydrochloric acid were added to the reactor, and the temperature was raised to 60°C and reacted for 6 hours. After the reaction was completed, the mixture was cooled to room temperature, washed with water until it became neutral, and then dried in a vacuum to obtain an amino-containing solid-phase synthesis support. The amino content of the obtained amino solid-phase synthesis support was 543 μmmol / g, and the average pore diameter measured by mercury intrusion porosimetry was 48 nm. EXAMPLES
[0038] 2L of purified water, 20g of polyvinyl alcohol, and 60g of sodium chloride were added to a 3L reactor equipped with a condenser, a stirrer, and a thermometer, and dissolved to obtain an aqueous phase. 70g of methylstyrene, 28g of divinylbenzene (content 80% by weight), 14g of p-chloromethylstyrene, 28g of 1,4-dicyano-2-butene, 6g of sorbitan trioleate, 45g of isooctanol, 30g of toluene, and 1g of benzoyl peroxide were weighed and mixed uniformly to obtain an oil phase. The oil phase was added to the reactor, stirred, heated to 70°C, and polymerized for 8 hours. After the reaction was completed, the mixture was washed with hot water, refluxed with ethanol to extract and remove the pore-forming agent, sieved to collect resin with a particle size of 50 to 100 μm, and vacuum dried to obtain a polymeric porous resin with a chlorine content of 660 μmmol / g. 50g of polymeric porous resin and 500ml of N,N-dimethylformamide were put into a 1L reactor equipped with a condenser, a stirrer and a thermometer, and stirred. Then, 35g of phthalimide potassium salt was added, and the temperature was raised to 95°C and reacted for 16 hours. After the reaction was completed, it was cooled to room temperature, and then washed twice with N,N-dimethylformamide, washed with purified water until it became neutral, and then washed three times with absolute ethanol, and the resin was filtered and dried. 200g of absolute ethanol and 50g of hydrazine hydrate were added to the reactor, and the temperature was raised to 75°C and reacted for 16 hours. After the reaction was completed, it was washed three times with a volume ratio of 50:50 ethanol / purified aqueous solution, washed with purified water until it became neutral, then washed three times with absolute ethanol, and the washing liquid was filtered. 200g of absolute ethanol and 50g of concentrated hydrochloric acid were added to the reactor, and the temperature was raised to 60°C and reacted for 6 hours. After the reaction was completed, the product was cooled to room temperature, washed with water until it became neutral, and then dried in a vacuum to obtain an amino-containing solid-phase synthesis support. The amino content of the obtained amino solid-phase synthesis support was 650 μmmol / g, and the average pore diameter measured by mercury intrusion porosimetry was 132 nm. EXAMPLES
[0039] 2L of purified water, 20g of polyvinyl alcohol, and 60g of sodium chloride were added to a 3L reactor equipped with a condenser, a stirrer, and a thermometer, and dissolved to obtain an aqueous phase. 127g of ethylstyrene, 4g of divinylbenzene (content 80% by weight), 8.8g of 4-(4-bromobutyl)styrene, 0.2g of transbutenedinitrile, 1g of polyoxyethylene sorbitol beeswax derivative, 12g of isooctanol, 12g of dibutyl phthalate, and 2.5g of benzoyl peroxide were weighed and mixed uniformly to obtain an oil phase. The oil phase was added to the reactor, stirred, heated to 65°C, and polymerized for 10 hours. After the reaction was completed, the mixture was washed with hot water, refluxed with ethanol to extract and remove the pore-forming agent, sieved to collect resin with a particle size of 50 to 100 μm, and vacuum dried to obtain a polymeric porous resin with a bromine content of 265 μmmol / g. 50g of polymeric porous resin and 600ml of N,N-dimethylformamide were added to a 1L reactor equipped with a condenser, stirrer and thermometer, and stirred. Then, 5.4g of 4-hydroxybenzoic acid, 5.4g of anhydrous potassium carbonate and 0.3g of potassium iodide were added. The temperature was raised to 75°C, and the reaction was carried out for 6 hours. After the reaction was completed, the mixture was cooled to room temperature, washed with water until it became neutral, and then dried in vacuum to obtain a solid-phase synthesis support containing hydroxyl. The obtained hydroxyl solid-phase synthesis support had a hydroxyl content of 250μmmol / g and an average pore diameter measured by mercury intrusion porosimetry of 23nm. EXAMPLES
[0040] 2L of purified water, 20g of polyvinyl alcohol, and 60g of sodium chloride were added to a 3L reactor equipped with a condenser, a stirrer, and a thermometer, and dissolved to obtain an aqueous phase. 110g of styrene, 11g of divinylbenzene (content 80% by weight), 9g of p-chloromethylstyrene, 10g of transbutene dinitrile, 0.5g of sorbitan tristearate, 20g of toluene, 40g of dibutyl phthalate, and 1g of benzoyl peroxide were weighed and mixed uniformly to obtain an oil phase. The oil phase was added to the reactor, stirred, heated to 60°C, and polymerized for 7 hours. After the reaction was completed, the mixture was washed with hot water, refluxed with ethanol to extract and remove the pore-forming agent, sieved to collect resin with a particle size of 50 to 100 μm, and vacuum dried to obtain a polymeric porous resin with a chlorine content of 425 μmol / g. 50g of polymeric porous resin and 300ml of anhydrous ethanol were put into a 1L reactor equipped with a condenser, a stirrer and a thermometer and stirred. 30g of sodium hydroxide was weighed into a beaker, dissolved in 300ml of deionized water and slowly added to the reactor. The temperature was raised to 65°C and reacted for 6 hours. After the reaction was completed, the mixture was cooled to room temperature, washed with water until neutral, and then vacuum dried to obtain a solid-phase synthesis support containing hydroxyl. The obtained hydroxyl solid-phase synthesis support had a hydroxyl content of 420μmmol / g and an average pore diameter of 43nm measured by mercury intrusion porosimetry. EXAMPLES
[0041] 2L of purified water, 20g of polyvinyl alcohol, and 60g of sodium chloride were added to a 3L reactor equipped with a condenser, a stirrer, and a thermometer, and dissolved to obtain an aqueous phase. 83g of styrene, 25g of divinylbenzene (content 80% by weight), 18g of N-(4-vinylphenyl)-acetamide, 14g of transbutene dinitrile, 3g of sorbitan tristearate, 16g of isooctanol, 8g of isododecane, and 2g of benzoyl peroxide were weighed and mixed uniformly to obtain an oil phase. The oil phase was added to the reactor, stirred, heated to 55°C, and polymerized for 10 hours. After the reaction was completed, the mixture was washed with hot water, refluxed with ethanol to extract and remove the pore-forming agent, sieved to collect resins with particle sizes of 50 to 100 μm, and vacuum-dried to obtain a polymeric porous resin. 50g of polymeric porous resin and 300ml of anhydrous ethanol were put into a 1L reactor equipped with a condenser, a stirrer and a thermometer and stirred. 30g of sodium hydroxide was weighed into a beaker, dissolved in 300ml of deionized water and slowly added to the reactor. The temperature was raised to 65°C and reacted for 6 hours. After the reaction was completed, the mixture was cooled to room temperature, washed with water until neutral, and then vacuum dried to obtain a solid-phase synthesis support containing amino. The obtained amino solid-phase synthesis support had an amino content of 840μmmol / g and an average pore diameter measured by mercury intrusion porosimetry of 43nm. EXAMPLES
[0042] 2L of purified water, 20g of polyvinyl alcohol, and 60g of sodium chloride were added to a 3L reactor equipped with a condenser, a stirrer, and a thermometer, and dissolved to obtain an aqueous phase. 111g of styrene, 11g of divinylbenzene (content 80% by weight), 13g of 4-acetoxystyrene, 5g of transbutenedinitrile, 8g of sorbitan monooleate, 40g of isooctanol, 20g of isododecane, and 2.5g of benzoyl peroxide were weighed and mixed uniformly to obtain an oil phase. The oil phase was added to the reactor, stirred, heated to 78°C, and polymerized for 6h. After the reaction was completed, the resin was washed with hot water, refluxed with ethanol to extract and remove the pore-forming agent, sieved to collect resin with a particle size of 50 to 100μm, and vacuum dried to obtain a polymer porous resin. 50g of polymeric porous resin and 300ml of acetonitrile were added to a 1L reactor equipped with a condenser, stirrer and thermometer and stirred. 7.5ml of hydrazine hydrate was slowly added and reacted at room temperature for 3h. After the reaction was completed, the mixture was washed with water until it became neutral, and then vacuum dried to obtain a solid-phase synthesis support containing hydroxyl. The obtained hydroxyl solid-phase synthesis support had a hydroxyl content of 550μmmol / g and an average pore diameter of 64nm measured by mercury intrusion porosimetry. EXAMPLES
[0043] 2L of purified water, 20g of polyvinyl alcohol, and 60g of sodium chloride were added to a 3L reactor equipped with a condenser, a stirrer, and a thermometer, and dissolved to obtain an aqueous phase. 130g of styrene, 5g of divinylbenzene (content 80% by weight), 4g of 4-acetoxystyrene, 1g of transbutene dinitrile, 1g of propylene glycol fatty acid ester, 40g of isooctanol, 10g of toluene, and 3.5g of benzoyl peroxide were weighed and mixed uniformly to obtain an oil phase. The oil phase was added to the reactor, stirred, heated to 70°C, and polymerized for 6h. After the reaction was completed, the resin was washed with hot water, refluxed with ethanol to extract and remove the pore-forming agent, sieved to collect resin with a particle size of 50 to 100 μm, and vacuum dried to obtain a polymer porous resin. 50g of polymeric porous resin and 300ml of acetonitrile were added to a 1L reactor equipped with a condenser, stirrer and thermometer and stirred. 7.5ml of hydrazine hydrate was slowly added and reacted at room temperature for 3h. After the reaction was completed, the mixture was washed with water until it became neutral, and then vacuum dried to obtain a solid-phase synthesis support containing hydroxyl. The obtained hydroxyl solid-phase synthesis support had a hydroxyl content of 175μmmol / g and an average pore diameter of 53nm measured by mercury intrusion porosimetry. EXAMPLES
[0044] 2L of purified water, 20g of polyvinyl alcohol, and 60g of sodium chloride were added to a 3L reactor equipped with a condenser, a stirrer, and a thermometer, and dissolved to obtain an aqueous phase. 72g of styrene, 28g of divinylbenzene (content 80% by weight), 27g of benzoyloxystyrene, 13g of transbutene dinitrile, 5g of hydroxylanolin, 10g of toluene, 20g of dibutyl phthalate, and 3g of benzoyl peroxide were weighed and mixed uniformly to obtain an oil phase. The oil phase was added to the reactor, stirred, heated to 80°C, and polymerized for 6h. After the reaction was completed, the resin was washed with hot water, refluxed with ethanol to extract and remove the pore-forming agent, sieved to collect resin with a particle size of 50 to 100 μm, and vacuum dried to obtain a polymer porous resin. 50g of polymeric porous resin and 300ml of acetonitrile were added to a 1L reactor equipped with a condenser, stirrer and thermometer and stirred. 7.5ml of hydrazine hydrate was slowly added and reacted at room temperature for 3h. After the reaction was completed, the mixture was washed with water until it became neutral, and then vacuum dried to obtain a solid-phase synthesis support containing hydroxyl. The obtained hydroxyl solid-phase synthesis support had a hydroxyl content of 852μmmol / g and an average pore diameter of 47nm measured by mercury intrusion porosimetry. EXAMPLES
[0045] 2L of purified water, 20g of polyvinyl alcohol, and 60g of sodium chloride were added to a 3L reactor equipped with a condenser, a stirrer, and a thermometer, and dissolved to obtain an aqueous phase. 85g of styrene, 24g of divinylbenzene (content 80% by weight), 18g of methyl 4-vinylbenzoate, 13g of transbutenedinitrile, 4g of polyoxyethylene sorbitol oleate, 40g of isododecane, 40g of dibutyl phthalate, and 2.5g of benzoyl peroxide were weighed and mixed uniformly to obtain an oil phase. The oil phase was added to the reactor, stirred, heated to 70°C, and polymerized for 6h. After the reaction was completed, the resin was washed with hot water, extracted by refluxing with ethanol, sieved to collect resins with particle sizes of 50 to 100 μm, and vacuum dried to obtain a polymeric porous resin. 50g of polymeric porous resin and 300ml of acetonitrile were added to a 1L reactor equipped with a condenser, stirrer and thermometer, and stirred. Then, 8.8g of hydroquinone, 23g of HBTU and 13ml of DIEA were added, and reacted at room temperature for 2 hours. After the reaction was completed, the mixture was washed with water until it became neutral, and then vacuum dried to obtain a solid-phase synthesis support containing hydroxyl. The obtained hydroxyl solid-phase synthesis support had a hydroxyl content of 735μmmol / g and an average pore diameter measured by mercury intrusion porosimetry of 143nm. EXAMPLES
[0046] The swelling degree of each of the solid phase synthesis supports produced in Examples 1 to 9 in acetonitrile and toluene was tested. The test was performed as follows. Approximately 1.5 g of a sample was weighed out and placed in a stoppered graduated cylinder, and toluene or acetonitrile was added to a specified mark. Then, the resin and the solvent were stirred with a glass rod to swell sufficiently, the stopper was tightened, and after 2 to 3 hours, the resin was gently stirred with a glass rod to remove air bubbles and disperse the resin evenly to avoid blocking, the stirring rod was removed, and the graduated cylinder was slammed on a table with a rubber mat to make the resin dense, and after leaving it for 24 hours, the volume was read and the swelling degree was calculated. The results are shown in Table 1. [Table 1] EXAMPLES
[0047] The performance of the resin was evaluated using the solid-phase synthesis support prepared in the examples and NittoPhase HL solid-phase synthesis support. In order to more intuitively express the advantages of the present invention, the support loading amount (g) = synthesis column volume (ml) / support swelling degree in toluene (ml / g), and the washing volume in the oligonucleotide synthesis process was limited to one synthesis column volume. 10 g of solid-phase synthesis support and 50 ml of acetonitrile were weighed in a reactor and allowed to swell for 10 min. Then, appropriate amounts of DMT-dT-3'-succinic acid, HBTU, and DIEA were added and reacted at room temperature for 12 h. After the reaction was completed, the support was washed five times with acetonitrile, and then Cap A (20 ml of acetonitrile, 7.5 ml of pyridine, and 5.0 ml of N-methylimidazole) and Cap B (10 ml of acetonitrile, 4 ml of acetic anhydride) were added and reacted at room temperature for 30 min. After the reaction was completed, the support was washed five times with acetonitrile and dried in vacuum to obtain a support carrying DMT-dT. The supported DMT group was removed using a p-toluenesulfonic acid / acetonitrile solution, and the amount of DMT group supported on the support was measured by spectrophotometry under 412 nm wavelength, and the results are shown in Table 2. The carrier carrying DMT-dT was packed into a synthesis column (32 ml), and the synthesis column was attached to an AKTA OligoPilot 100 to synthesize a 20-base-long oligonucleotide with the sequence d[ACGTACGTACGTACGTACGT]. The synthesis process was as follows: 1. The resin was swollen with dichloromethane. 2. The DMT group was removed with 10% DCA / DCM. 3. It was washed with anhydrous acetonitrile. 4. A phosphoramidite monomer and an activating reagent were added and condensed. 5. It was washed with anhydrous acetonitrile. 6. It was oxidized by adding an oxidizing agent. 7. It was washed with anhydrous acetonitrile. 8. It was capped by adding a capping reagent. 9. It was washed with anhydrous acetonitrile. 10. Step 2 was repeated to start the next cycle. After the synthesis was completed, the support was removed and dried. It was then placed in a glass bottle, and an appropriate amount of concentrated aqueous ammonia was added and reacted at 55°C for 16 hours to decompose and remove the oligonucleotide from the support, and to remove the protecting group at the base. The support and oligonucleotide were separated by filtration, and the filtrate was dried to obtain crude oligonucleotide powder. The purity was detected by HPLC, and the yield of the oligonucleotide was calculated. The results are shown in Table 2. [Table 2]
[0048] As can be seen from Table 2, the oligonucleotide solid phase synthesis support of the present invention can improve the yield and purity of oligonucleotide, which is advantageous for reducing the production cost of oligonucleotide.
[0049] It should be noted that the above is merely a preferred embodiment of the present invention, and those skilled in the art may make some modifications and improvements without departing from the concept of the present invention, all of which fall within the scope of protection of the present invention.
Claims
1. A porous resin for solid phase synthesis, the porous resin being a copolymer having repeating structural units represented by formula (I), formula (II), formula (III), or formula (IV) in its skeleton, 【Chemistry 1】 (However, R 4 =-C- or -C-CH 2 - is.) 【Chemistry 2】 【Chemistry 3】 (However, R 5 is -OH, -CH 2 OH, -NH 2 , -CH 2 NH 2 , -CH 2 OOC-C 6 H 4 -OH, -CH 2 OOCC H 2 -C 6 H 4 -OH, -(CH 2 ) 4 OOC-C 6 H 4 -OH, -(CH 2 ) 4 OOCC H 2 -C 6 H 4 -OH, -CONH-C 6 H 4 -NH 2 , -CH 2 CONH-C 6 H 4 -NH 2 , -COO-C 6 H 4 -OH, or -CH 2 COO-C 6 H 4 -OH.) 【Chemistry 4】 (However, R 6 H, CH 3 (CH 2 ) n - (n is an integer from 0 to 4), (CH 3 ) 2 CH (CH 2 ) n - (n is an integer from 0 to 2), (CH 3 ) 3 C-, CH 3 CH 2 CH (CH 3 ) -, CH 3 CH 2 C (CH 3 ) 2 -, CH 3 CH 2 CH 2 CH (CH 3 ) - or CH 3 (CH 2 ) n -O- (n is an integer from 0 to 4). (The repeating structural units represented by formula (I), formula (II), formula (III), and formula (IV) are derived from a modifying monomer, a crosslinking monomer, a functional monomer, and a monovinyl compound, respectively.) (However, the amount of the monovinyl compound is 40 to 95.9% by weight based on the total amount of monomers, the amount of the crosslinking monomer is 2 to 20% by weight based on the total amount of monomers, the amount of the functional monomer is 2 to 20% by weight based on the total amount of monomers, and the amount of the modified monomer is 0.1 to 20% by weight based on the total amount of monomers.) (Note that the porous resin has a hydroxy or amino content of 100 to 1000 μmol / g, and the amino or hydroxy content is obtained by reacting with Fmoc-Leu-OH and then removing the Fmoc protecting group, and the amount of Fmoc removed is determined by colorimetry to calculate the amino or hydroxy content in the porous resin.) The porous resin is detected by a particle image processing device, that is, the porous resin is uniformly distributed on a slide glass, and while the carrier particles are magnified by a microscope, a particle image of the porous resin magnified by the microscope is taken by a camera, and the appearance characteristics and particle size of the porous resin are analyzed by a computer to calculate a particle size range of 35 to 200 μm; The porous resin is characterized in that the average pore size of the porous resin is measured by mercury intrusion porosimetry, i.e., 0.1500 to 0.3000 g of a sample is accurately weighed and placed in a fully automatic mercury intrusion apparatus AutoPore IV 9500 (Micromeritics Instrument Co.), the contact angle of mercury is set to 130°, and the surface tension is set to 485 dyn / cm, and the average pore size of the porous resin for solid-phase synthesis measured by mercury intrusion porosimetry under these conditions is 10 to 200 nm.
2. The porous resin for solid phase synthesis according to claim 1, characterized in that the content of hydroxy or amino is 400-700 μmol / g, said content of amino or hydroxy is obtained by reacting with Fmoc-Leu-OH and then removing the Fmoc protecting group, and determining the amount of removed Fmoc by colorimetry to calculate said content of amino or hydroxy in said porous resin.
3. The porous resin for solid phase synthesis described in claim 1, characterized in that the porous resin is detected by a particle image processing device, i.e., the porous resin is uniformly distributed on a slide glass, the carrier particles are magnified under a microscope, and a particle image of the porous resin magnified by the microscope is taken with a camera, and the appearance characteristics and particle size of the porous resin are analyzed by a computer to calculate a particle size range of 50 to 100 μm.
4. The porous resin for solid-phase synthesis according to claim 1, characterized in that the average pore size of the porous resin is measured by mercury intrusion porosimetry, i.e., 0.1500 to 0.3000 g of a sample is accurately weighed and placed in a fully automatic mercury intrusion apparatus AutoPore IV 9500 (Micromeritics Instrument Co.), the mercury contact angle is set to 130°, and the surface tension is set to 485 dyn / cm, and the average pore size measured by mercury intrusion porosimetry under these conditions is 40 to 100 nm.
5. A method for producing a porous resin for solid phase synthesis, comprising the steps of preparing an aqueous phase consisting of water, a dispersant, and an inorganic salt, and an oil phase consisting of a monovinyl compound, a crosslinking monomer, a functional monomer, a modified monomer, an oil-soluble surfactant, a diluent, and an initiator; adding the oil phase to the water phase, stirring and heating the mixture to polymerize the mixture; and removing the pore-forming agent after the polymerization reaction is completed to obtain a porous polymer resin. the monovinyl compound, the crosslinking monomer, the functional monomer and the modified monomer participate in the polymerization reaction, while the oil-soluble surfactant and the diluent do not participate in the polymerization reaction and mainly perform a pore-forming function; The modified monomer includes transbutene dinitrile and 1,4-dicyano-2-butene, The monovinyl compounds include styrene and its benzene ring substituted derivatives, the substituents being alkyl or alkoxy containing 1 to 5 carbon atoms; the cross-linking monomer is divinylbenzene; The functional monomers include 4-hydroxystyrene, 4-hydroxymethylstyrene, 4-acetoxystyrene, benzoyloxystyrene, 4-aminostyrene, 4-aminomethylstyrene, 4-(4-bromobutyl)styrene, p-chloromethylstyrene, 4-vinylbenzoic acid methyl ester, and 4-ethenylbenzene ethyl acetate; The diluent is an organic solvent that does not participate in the polymerization reaction, The dispersant is a water-soluble polymer, and includes one or more of polyvinyl alcohol, hydroxyethyl cellulose, hydroxyethyl methyl cellulose, carboxymethyl cellulose, sodium polyacrylate, and polyvinylpyrrolidone; In the oil phase, the monovinyl compound is present in an amount of 40 to 95.9% by weight based on the total amount of monomers; In the oil phase, the cross-linking monomer is 2 to 20% by weight based on the total amount of monomers; In the oil phase, the functional monomer is present in an amount of 2 to 20% by weight based on the total amount of monomers; In the oil phase, the modified monomer is present in an amount of 0.1 to 20% by weight based on the total amount of monomers; Further reacting the porous polymer resin to obtain a porous resin containing hydroxy or amino as a functional group, the porous resin has a hydroxy or amino content of 100-1000 μmol / g, the amino or hydroxy content being obtained by reacting with Fmoc-Leu-OH and then removing the Fmoc protecting group, the amount of Fmoc removed being determined by colorimetry, and the amino or hydroxy content in the porous resin being calculated; The porous resin is detected by a particle image processing device, that is, the porous resin is uniformly distributed on a slide glass, and while the carrier particles are magnified by a microscope, a particle image of the porous resin magnified by the microscope is taken by a camera, and the appearance characteristics and particle size of the porous resin are analyzed by a computer to calculate a particle size range of 35 to 200 μm; The porous resin is measured by mercury intrusion porosimetry, i.e., 0.1500 to 0.3000 g of a sample is accurately weighed and placed in a fully automatic mercury intrusion apparatus AutoPore IV 9500 (Micromeritics Instrument Co.), the contact angle of mercury is set to 130°, and the surface tension is set to 485 dyn / cm. The average pore size measured by mercury intrusion porosimetry under these conditions is 10 to 200 nm.
6. The method for producing a porous resin for solid phase synthesis as described in claim 5, characterized in that the initiator is an organic peroxide or an azo compound.
7. The method for producing a porous resin for solid phase synthesis described in claim 6, characterized in that the initiator includes benzoyl peroxide, lauroyl peroxide, t-butylperoxy 2-ethylhexanoate, 2,2'-azobis(2-methylpropionitrile), 2,2'-azobis(2-methylbutyronitrile), and 2,2'-azobis(2,4-dimethylvaleronitrile).
8. The method for producing a porous resin for solid phase synthesis described in claim 5, characterized in that the oil-soluble surfactant includes one or a combination of more of sorbitan trioleate, polyoxyethylene sorbitol beeswax derivatives, sorbitan tristearate, polyoxyethylene sorbitol hexastearate, ethylene glycol fatty acid esters, propylene glycol fatty acid esters, propylene glycol monostearate, sorbitan sesquioleate, polyoxyethylene sorbitol oleate, glyceryl monostearate, hydroxylanolin, sorbitan monooleate, and propylene glycol monolaurate.
9. The method for producing a porous resin for solid phase synthesis described in claim 5, characterized in that the diluent includes benzene, toluene, ethylbenzene, hexane, heptane, octane, dodecane, isooctane, isododecane, cyclohexane, chloroform, chlorobenzene, ethyl acetate, butyl acetate, dibutyl phthalate, hexanol, cyclohexanol, octanol, isooctanol, decanol, and dodecanol.
10. In the aqueous phase, the dispersant is present in an amount of 0.1 to 5% by weight, and the inorganic salt is present in an amount of 20% by weight or less. the weight ratio of the oil phase to the aqueous phase is 1:3 to 1:20; In the oil phase, the weight of the pore-forming agent is 15 to 70% of the total weight of the monomers; In the pore-forming agent, the oil-soluble surfactant accounts for 0.1 to 15% of the total weight of the pore-forming agent; 6. The method for preparing a porous resin for solid phase synthesis according to claim 5, wherein the diluent in the pore-forming agent accounts for 85 to 99.9% of the total weight of the pore-forming agent.
11. The method for producing a porous resin for solid phase synthesis according to claim 5, wherein the polymerization temperature is 50 to 90°C.
12. The manufacturing process includes: Adding a certain amount of purified water to a reactor, adding and dissolving 0.1 to 5% by weight of the dispersant and 20% by weight or less of the inorganic salt relative to the weight of the aqueous phase to obtain the aqueous phase; weighing and uniformly mixing the monovinyl compound at 40-95.9%, the crosslinking monomer at 2-20%, the functional monomer at 2-20%, the modified monomer at 0.1-20%, the oil-soluble surfactant at 0.1-15% by weight and the diluent at 85-99.9% by weight relative to the total weight of the monomers, and the initiator, to obtain the oil phase, so that the weight ratio of the oil phase to the water phase is 1:3-1:20; The method for preparing the porous resin for solid phase synthesis according to any one of claims 5 to 11, further comprising the steps of: adding the oil phase to the reactor, stirring and heating to 50-90°C, reacting, removing the pore-forming agent after the reaction is completed, sieving to collect resin with an appropriate particle size, vacuum drying to obtain a porous polymer resin, and further reacting the resin to obtain a porous resin with amino or hydroxy functional groups.
13. The process for producing the porous amino resin comprises the steps of: 2 L of purified water, 20 g of polyvinyl alcohol, and 60 g of sodium chloride were charged into a 3 L reactor equipped with a condenser, a stirrer, and a thermometer, and dissolved to obtain an aqueous phase. Weigh out 110g of styrene, 10g of divinylbenzene (content 80% by weight), 12g of p-chloromethylstyrene, 8g of transbutene dinitrile, 5g of sorbitan monooleate, 45g of isooctanol and 2.5g of benzoyl peroxide, and mix them uniformly to obtain an oil phase. The oil phase is added to a reactor, stirred, heated to 80°C, and polymerized for 4 hours. After the reaction is completed, the mixture is washed with hot water, and the pore-forming agent is extracted and removed by refluxing ethanol. The mixture is sieved to collect the resin with a particle size of 50-100 μm, and then vacuum dried to obtain a polymer porous resin with a chlorine content of 550 μmol / g. 50 g of polymeric porous resin and 500 ml of N,N-dimethylformamide were put into a 1 L reactor equipped with a condenser, a stirrer and a thermometer, and stirred. Then, 30 g of phthalimide potassium salt was added, and the temperature was raised to 95° C. and reacted for 16 hours. After the reaction was completed, the mixture was cooled to room temperature, and then washed twice with N,N-dimethylformamide, washed with purified water until it became neutral, and then washed three times with absolute ethanol. The resin was filtered and dried, and 200 g of absolute ethanol and 50 g of hydrazine hydrate were added to the reactor, and the temperature was raised to 75° C. reacting for 16 hours, washing three times with ethanol / purified water solution in a volume ratio of 50:50 after the reaction is complete, washing with purified water until neutral, then washing three times with absolute ethanol, filtering and removing the washing liquid, adding 200 g of absolute ethanol and 50 g of concentrated hydrochloric acid to the reactor, heating to 60° C. and reacting for 6 hours, cooling to room temperature after the reaction is complete, washing with water until neutral, and then drying in a vacuum to obtain a solid-phase synthesis support having an amino content of 543 μmol / g and an average pore size of 48 nm as measured by mercury intrusion porosimetry, or The process for producing the porous hydroxy resin comprises: 2 L of purified water, 20 g of polyvinyl alcohol, and 60 g of sodium chloride were charged into a 3 L reactor equipped with a condenser, a stirrer, and a thermometer, and dissolved to obtain an aqueous phase. 111g of styrene, 11g of divinylbenzene (content 80% by weight), 13g of 4-acetoxystyrene, 5g of transbutene dinitrile, 8g of sorbitan monooleate, 40g of isooctanol, 20g of isododecane and 2.5g of benzoyl peroxide are weighed and mixed uniformly to obtain an oil phase, the oil phase is added to a reactor, stirred and heated to 78°C, and polymerized for 6 hours, after the reaction is completed, the resin is washed with hot water, and the pore-forming agent is extracted and removed by refluxing ethanol, and the resin with a particle size of 50-100 μm is collected by sieving, and then vacuum dried to obtain a polymer porous resin; 13. A method for producing a porous resin for solid-phase synthesis according to claim 5, comprising the steps of: putting 50 g of the polymeric porous resin and 300 ml of acetonitrile into a 1 L reactor equipped with a condenser, a stirrer and a thermometer, stirring, slowly adding 7.5 ml of hydrazine hydrate, reacting at room temperature for 3 hours, washing with water until neutral after the reaction is completed, and then drying in vacuum to obtain a hydroxy-containing solid-phase synthesis support having a hydroxy content of 550 μmol / g and an average pore diameter of 64 nm measured by mercury intrusion porosimetry.
14. 14. Use of the porous resin for solid-phase synthesis according to claim 1, produced by the method according to any one of claims 5 to 13, in solid-phase synthesis of oligonucleotides.
15. The method for producing a porous resin for solid phase synthesis according to claim 5, characterized in that in the oil phase, the monovinyl compound is 60 to 88% by weight based on the total amount of monomers.
16. The method for producing a porous resin for solid phase synthesis as described in claim 5, characterized in that in the oil phase, the cross-linking monomer is 5 to 15% by weight relative to the total amount of monomers.
17. The method for producing a porous resin for solid phase synthesis as described in claim 5, characterized in that in the oil phase, the functional monomer is 5 to 15 weight % relative to the total amount of monomers.
18. The method for producing a porous resin for solid phase synthesis as described in claim 5, characterized in that in the oil phase, the modified monomer is 2 to 10% by weight relative to the total amount of monomers.
19. The method for producing a porous resin for solid phase synthesis as described in claim 5, characterized in that in the oil phase, the weight of the pore-forming agent is 25 to 50% of the total weight of the monomers.
20. The method for producing a porous resin for solid phase synthesis according to claim 5, characterized in that the polymerization temperature is 60 to 85°C.
21. The manufacturing process comprises: Adding a certain amount of purified water to a reactor, adding and dissolving the dispersant in an amount of 0.1 to 5% by weight based on the weight of the aqueous phase and the inorganic salt in an amount of 20% by weight or less based on the weight of the aqueous phase to obtain the aqueous phase; weighing and uniformly mixing the following, based on the total weight of the monomers: 60-88% by weight of the monovinyl compound, 5-15% by weight of the crosslinking monomer, 5-15% by weight of the functional monomer, 2-10% by weight of the modified monomer, 25-50% by weight of the pore-forming agent, in which the oil-soluble surfactant accounts for 0.1-15% by weight and the diluent accounts for 85-99.9% by weight based on the weight of the pore-forming agent, and the initiator, so that the weight ratio of the oil phase to the water phase is 1:3-1:20, thereby obtaining the oil phase; The method for preparing the porous resin for solid phase synthesis according to any one of claims 5 to 11, further comprising the steps of: adding the oil phase to the reactor, stirring and heating to 60-85°C, reacting; after the reaction is completed, removing the pore-forming agent, sieving to collect resin with suitable particle size, and vacuum drying to obtain a porous polymer resin; and further reacting the resin to obtain a porous resin with amino or hydroxy functional groups.
Citation Information
Patent Citations
Production of 1,4-dicyano-2-butene
JP1994306037A
Polymer beads for oligomer synthesis
JP2008511743A
Porous resin bead and production method of nucleic acid using the same
JP2010006888A
Porous resin bead and method for producing nucleic acid using the same
JP2011063728A
Lithium-ion rechargeable battery
JP2013539905A